Confiscation of unregistered medicines: time to empower health education - Ahmad Mahfuz, Gazali (Social Health Analytics Sdn Bhd, 2025)
Most Malaysians are unaware of the consequences of health problems that may affect them. Health Minister Dr Dzulkefly Ahmad recently reported that RM37.5 million unregistered medicines were confiscated last year. This trend is worrying, as it marks an increase in confiscated unregistered medicines from 21,517 in 2024 to 20,157 in 2023. He presented this fact during the launch of the Reject Illegal Medicines Roadshow for Central Zone on May 3, 2025.